FAKTOR-FAKTOR YANG MEMPENGARUHI PERSONAL HYGIENE PADA SISWA DALAM MANAJEMEN LAYANAN USAHA KESEHATAN SEKOLAH (UKS) SMK GANDA HUSADA TEBING TINGGI TAHUN 2022 - FITHRI HANDAYANI LUBIS; hengki frengki manullang (Fakultas Kesehatan Masyarakat Institut Kesehatan Deli Husada Delitua, 2022)
Personal hygiene comes from the Greek words meaning individual, and cleanliness, meaning health. Personal hygiene is taking care of your body to improve your physical and mental health. Clean and healthy living behavior is behavior done by the community to take care of their own health and play an active role in maintaining the cleanliness and health of the environment. Poor personal hygiene can cause various diseases such as diarrhea, tooth decay, and asthma. The purpose of this study is to find out the effect of personal hygiene on school health services. The research design used is descriptive observation with a qualitative approach. Sampling is done using the probability sampling method. The survey method is a questionnaire. This data was analyzed using chi-square statistical analysis. The results of this study indicate that there is an influence between knowledge and personal hygiene with a P value of 0.004. There is an Influence of Attitude with Personal Hygiee at SMK Ganda Husada Tebing Tinggi with a P value of 0.001. There is an influence of Educator Support with Personal Hygiene with P value of 0.003. There is an influence of family support with personal hygiene with a P value of 0.003. There is an influence of PHBS Facilities with Personal Hygiene with a P value of 0.004. In schools, it is recommended that personal hygiene education be taught more in accordance with the school curriculum. Schools can collaborate with local start-ups through the UKS program and conduct regular personal hygiene sessions